Great saphenous varicose vein treatment with endovenous ablation techniques: A comparison of EVLA and RF (Annals of Medical Research, 2021)
Aim: In this study, we compared the clinical follow-up results and complication and success rates of patients undergoing 1470 nm wavelength endovenous laser ablation (EVLA) or radiofrequency ablation (RFA) in our clinic.Material and Methods: The records of 581 patients treated in our clinic due to clinical symptoms arising from great saphenous vein insufficiency between January 2014 and September 2018 were examined retrospectively. Three hundred fifty-seven of these patients treated with EVLA or RFA and with no deficient data were included in the study. Patients with reflux in the saphenofemoral junction lasting at least 0.5 sec, with a great saphenous vein diameter of at least 7 mm, 2 cm distal to the saphenofemoral junction, and of at least 5.5 mm at knee level, and with CEAP stage C2-C5 were scheduled for endovenous ablation. The patients were randomly distributed between the established EVLA and RFA treatment groups. Data for patients’ diagnostic and therapeutic processes were recorded and evaluated in the light of information in the literature. Results: The EVLA group consisted of 86 patients (42 male, 44 female; mean age 46 years, range 26-71), and the RFA group of 271 (113 male, 158 female; mean age 43.3 years; range 20-77). The mean follow-up time was 27.2 months. No significant differences were determined in terms of patients’ demographic data, preoperative additional diagnoses, CEAP classification values, duration of reflux, or proximal and distal great saphenous vein diameter values. Thrombophlebitis developed in 14 patients and ecchymosis/hematoma in 32. No significant difference was observed between the groups in terms of complications. Great saphenous vein occlusion rates at Doppler ultrasonography six months after treatment were 91.8% in the EVLA group and 94% in the RFA group (p=0.46). Conclusion: Our results suggest that neither of the two endovenous ablation methods is superior to the other.